Recent Potential Treatment Approaches for the Management of Uveitis - Nikita; Yasmin Sultana (Journal of Clinical Research and Ophthalmology - Peertechz Publications, 2020)
Uveitis, an inflammatory condition of the eye affecting the uvea [blood vessel-rich middle layer of tissue] may lead to slight or complete vision loss. This disease can affect people of any age group mainly between 20 to 60 years of age. It is reported that 24.9 cases per 100,000 persons were affected in a study in the years 2006 and 2007 with a prevalence rate of 57.5 and 58 per 100,000 persons respectively [1,2].